2017
DOI: 10.1186/s13063-017-2163-5
|View full text |Cite
|
Sign up to set email alerts
|

A primary school active break programme (ACTI-BREAK): study protocol for a pilot cluster randomised controlled trial

Abstract: BackgroundLevels of overall physical activity have been shown to decline across childhood. Schools are considered ideal settings to promote physical activity as children spend a large amount of their waking hours at school. Time-efficient physical activity strategies that demonstrate a positive impact on academic-related outcomes are needed to enable physical activity to be prioritised in the school day. The ACTI-BREAK programme requires classroom teachers to integrate active breaks; 5-min bursts of moderate-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 48 publications
1
40
0
2
Order By: Relevance
“…An alternative explanation for implementation at a mainly light-intensity may relate to teacher concerns for moderate-intensity active breaks to have an adverse effect on behaviour. While in the development phase teachers considered moderate-intensity active breaks to be feasible [19], results of this study suggest that in practice teachers prefer light-intensity active breaks, perhaps due to the perception that came out in the interviews that students (particularly those with behavioural challenges) were easier to settle following light-, compared with moderate-intensity active breaks. In contrast, previous studies have consistently reported moderate- to vigorous-intensity active breaks had a positive acute effect on behaviour [6] and one indicated that behaviour improved most for those the most off task prior to active break sessions [27].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…An alternative explanation for implementation at a mainly light-intensity may relate to teacher concerns for moderate-intensity active breaks to have an adverse effect on behaviour. While in the development phase teachers considered moderate-intensity active breaks to be feasible [19], results of this study suggest that in practice teachers prefer light-intensity active breaks, perhaps due to the perception that came out in the interviews that students (particularly those with behavioural challenges) were easier to settle following light-, compared with moderate-intensity active breaks. In contrast, previous studies have consistently reported moderate- to vigorous-intensity active breaks had a positive acute effect on behaviour [6] and one indicated that behaviour improved most for those the most off task prior to active break sessions [27].…”
Section: Discussionmentioning
confidence: 89%
“…The ACTI-BREAK intervention was designed in consultation with current primary school teachers, and involved classroom teachers incorporating 3 × 5-minute active breaks into their classroom routine daily [19]. Additional detail on the intervention development is provided in the trial protocol [19]. The intervention aimed to improve on-task behaviour, academic achievement and school-based physical activity levels [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each activity card was designed to last for 30 s with ABs recommended to last for five minutes in total. This time period was chosen to cause minimal disruption to class time and it was used in a pilot of a primary school AB programme (ACTI-BREAK) as outlined by Watson et al, 2017 [30]. The ACTI-BREAK pilot study, in which participating schools were instructed to implement five-minute ABs three times per day, did not have an effect on PA levels [31].…”
Section: Methodsmentioning
confidence: 99%
“…Since children spend most of their time at school, this context presents a great opportunity for improvement and to increasephysical activity [15]. Opportunities for physical activity at school ariseduring the physical education session [20,21], through the teaching of other curricular contents [15,22], and during the breaks that occur during the school day [9,23,24,25].…”
Section: Introductionmentioning
confidence: 99%